The intercarotid or alar fascia, other cervical fascias, and their adjacent spaces - a plea for clarification of cervical fascia and spaces terminology - Feigl, Georg; Hammer, Georg P; Litz, Rainer; Kachlik, David (Journal of anatomy, 2020)
Due to varying descriptions and terminology of fascias of the neck, medical advice relying on this basic knowledge is insufficient. Our goal was to provide a precise anatomical description of cervical fascias and spaces with special focus on the intercarotid fascia, or the alar fascia. One hundred bodies donated to science embalmed with Thiel's method were investigated, cervical fascias were dissected layer by layer, and the results were documented by photography, with a focus on the intercarotid fascia. In addition, we performed a review of recent literature concerning cervical surgical interventions, radiological diagnostic pathways, and basic anatomical works focusing on core information on anatomical relations of cervical fascias and spaces. In another 10 bodies donated to science, the spaces of the neck were injected with coloured latex under ultrasound guidance, dissected, and documented by photography. The intercarotid fascia was a constantly developed connective tissue interconnecting the carotid sheath of both sides. In 52 of 100 specimens (52%) it crossed to the opposite side without any fusion to the ventrally situated visceral fascia. Fusion with the visceral fascia was found in 48%, either at the lateral border of the pharynx or on its dorsal side. The results of our dissections strengthen the precise description of the cervical fascias provided by Grodinsky and Holyoke in 1938. Spaces can be confirmed as described by Hafferl in 1969. The international anatomical and ENT societies should codify a unified anatomical terminology of the cervical spaces and fascias to prevent varying interpretations in the future.
Keywords: fascia alaris; Humans; head and neck; mrtvola; Fascia; Neck; neck anatomy; krk; cervical abscess; fascia cervicalis; fascia intercarotica; intercarotid fascia; fascie; alar fascia; cervical fascia; Cadaver; lidé